Foreign Policy : Theories, Actors, Cases - Edited by Smith, Steve ; Hadfield, Amelia & Dunne, Tim (UK Oxford University Press, 2016)
The only introduction to foreign policy to combine theories, actors and cases in one volume.
Include Illustrations and Index
Keywords: International relations -- International relations--Research